Narrative Network Analysis on Social Media Concerning the XYZ Ministry in Indonesia: Constructive Criticism vs. 'Pseudo-Haters' - Said, Martriana Ponimin; Rospitasari, Marina (Jogjakarta Communication Conference (JCC), 2025)
This article analyses the network of narratives circulating on social media regarding the XYZ Ministry in Indonesia, focusing on distinguishing between constructive criticism and the activities of